The epidemiology of substance use disorders in Saudi Arabia: findings from the Saudi national mental health survey - Yasmin Altwaijri; Corina Benjet; Marya Akkad; Lisa Bilal; Mohammad Talal Naseem; Abdulhameed Al-Habeeb; Abdullah S. Al-Subaie; Nouf K. Al-Saud (BMC Public Health)
Abstract Background Substance use disorders (SUDs), encompassing alcohol (AUDs) and drug use disorders (DUDs), are significant global public health concerns. While SUDs are well-documented worldwide, data on their prevalence and impact in Saudi Arabia remain scarce. This study investigates the epidemiology and burden of SUDs in Saudi Arabia using data from the Saudi National Mental Health Survey (SNMHS). Methods The SNMHS is a nationally representative cross-sectional epidemiological household survey, consisting of a sample of 4,004 participants aged 15–65. The survey employed a stratified multistage clustered sampling design and used the WHO CIDI 3.0 to determine diagnoses. Descriptive statistics and multivariate binary logistic regression were used to analyze the data. Results The lifetime, 12-month, and 30-day prevalence of any SUD were 4.03%, 1.88%, and 0.78% (p < 0.05), respectively. DUDs were more prevalent than AUDs overall. SUDs were significantly associated with younger age, lower education, low income, exposure to traumatic events, family burden, and childhood adversities. High psychiatric comorbidity and role impairment were observed. Treatment seeking was moderate, with only 44.9% of those with lifetime SUDs seeking any form of treatment. Conclusions SUDs in Saudi Arabia are more prevalent than previously thought, associated with significant psychiatric comorbidities and role impairment. Despite this, treatment seeking remains inadequate. These findings underscore the need for targeted prevention and intervention programs tailored to the demographic and cultural context of Saudi Arabia.